2019
DOI: 10.1002/jac5.1177
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the primary care clinical pharmacy specialist: Increasing patient access and quality of care within the Veterans Health Administration

Abstract: Background Access to high‐quality care is a US Department of Veterans Affairs (VA) top priority. The VA utilized the principles of the Patient Centered Medical Home model to design the Patient‐Aligned Care Team (PACT) to deliver primary care to our nation's Veterans. The PACT model was introduced in the VA in 2009 and was implemented across the health care system in 2010. Objective This review will highlight how the VA clinical pharmacy specialist (CPS) have been integrated throughout the VA to provide clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 8 publications
0
31
0
Order By: Relevance
“…In this role, they can improve access, lower costs, and reduce PCP burden. 19,47 By contrast, consultative integration is partial integration. While a CPS who is seen as auxiliary support for PCPs might free up PCP time by answering questions rapidly, 48 positioning CPS as medication consultants uses only part of their skillset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this role, they can improve access, lower costs, and reduce PCP burden. 19,47 By contrast, consultative integration is partial integration. While a CPS who is seen as auxiliary support for PCPs might free up PCP time by answering questions rapidly, 48 positioning CPS as medication consultants uses only part of their skillset.…”
Section: Discussionmentioning
confidence: 99%
“…18 CPS are advanced practice providers with the authority to prescribe and modify medications, but they do not diagnose, so PCP-pharmacist collaboration is essential. 18,19 CPS have worked in the VHA since the early 1990s, primarily managing diseases (eg, diabetes, hypertension, and lipids) in isolation, or specific medications (eg, warfarin). [20][21][22] However, CPS' training also prepares them to manage patients' multiple disease states using comprehensive medication management (CMM), which includes assessing patients' medication needs, adding drug therapies as necessary, titrating doses to achieve therapeutic levels, and assessing the appro-priateness, effectiveness, and safety across all their medications (prescription, nonprescription, alternative, traditional, vitamins, and nutritional supplements).…”
Section: Introductionmentioning
confidence: 99%
“…Starting in FY2017, virtual care encounters began to outpace in‐person encounters each year with the most dramatic increase in FY 2020. Previous literature has shown that VA CPS practicing in primary care have been increasingly utilizing virtual care modalities which accounted for 59% of patient care encounters in 2019 11 …”
Section: Clinical Pharmacy Practice Integration Of Virtual Carementioning
confidence: 99%
“…Soon after, a CDTM law was passed in Washington state in 1979 and prescriptive authority for pharmacists was adopted by the Veterans Health Administration (VHA) 17 . Since then, the number of pharmacists with prescriptive authority practicing in the VHA system has grown to 4259 as of 2019 18 …”
Section: Collaborative Practice Agreementsmentioning
confidence: 99%